The Holy Qur`an, published in the printing house of “Terdzhiman” in the Crimea in the late XIX – early XX centuries - Amin Alkasem (Крымское историческое обозрение)
The article describes the history of the Koran, published by the “Terdzhiman” printing house in Bakhchisarai in the late XIX – early XX centuries. The author analyzed the peculiarities, reviewed the types and number of copies of the Muslim holy book published by I. Gasprinsky, as well as provides data on the copies of the Bakhchisarai press that have survived today.